2005
DOI: 10.1111/j.1471-4159.2004.02949.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Akt/PKB, increased phosphorylation of Akt substrates and loss and altered distribution of Akt and PTEN are features of Alzheimer's disease pathology

Abstract: Studies suggest that activation of phosphoinositide 3-kinaseAkt may protect against neuronal cell death in Alzheimer's disease (AD). Here, however, we provide evidence of increased Akt activation, and hyperphosphorylation of critical Akt substrates in AD brain, which link to AD pathogenesis, suggesting that treatments aiming to activate the pathway in AD need to be considered carefully. A different distribution of Akt and phospho-Akt was detected in AD temporal cortex neurons compared with control neurons, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
284
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(323 citation statements)
references
References 41 publications
24
284
0
2
Order By: Relevance
“…For example, PI3K/mTOR signaling regulates Tau phosphorylation (24), and mTOR activation enhances Tau-induced neurodegeneration in a Drosophila model of tauopathies (78). Further strengthening the mTOR/Tau link are the data resulting from investigations of AD brains showing that mTOR signaling is selectively increased in neurons predicted to develop neurofibrillary tangles and that such an increase correlates with Tau phosphorylation (25)(26)(27)(28). This evidence has led to the hypothesis that the chronic increase in mTOR function occurring during aging may facilitate the development of Tau pathology (27).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, PI3K/mTOR signaling regulates Tau phosphorylation (24), and mTOR activation enhances Tau-induced neurodegeneration in a Drosophila model of tauopathies (78). Further strengthening the mTOR/Tau link are the data resulting from investigations of AD brains showing that mTOR signaling is selectively increased in neurons predicted to develop neurofibrillary tangles and that such an increase correlates with Tau phosphorylation (25)(26)(27)(28). This evidence has led to the hypothesis that the chronic increase in mTOR function occurring during aging may facilitate the development of Tau pathology (27).…”
Section: Discussionmentioning
confidence: 97%
“…insulin/insulin-like growth factor, cell energy status, nutrients, and stress) via different signaling transduction pathways (11), some of which are modulated by A␤ (20 -24). Indeed, evidence from AD brains shows that mTOR signaling is selectively increased in neurons predicted to develop neurofibrillary tangles and that such an increase correlates with Tau phosphorylation (25)(26)(27)(28). This evidence has led to the hypothesis that the chronic increase in mTOR function occurring during aging may facilitate the development of Tau pathology (27).…”
mentioning
confidence: 99%
“…Conflicting results, however, have been reported for the activity of this pathway in sporadic AD. Zunbenco et al (1999) reported reduced PI3K activity in AD brain tissue, whereas Griffin et al (2005) reported increased Akt phosphorylation in AD brain. Postmortem delays in the removal and processing of human brain tissue have been shown to affect both the stability and phosphorylation of many proteins (Ferrer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its ability to affect cell fate and activities by influencing survival and other central regulatory pathways, Akt has become a prominent point of focus in various fields of research ranging from tumorigenesis to diabetes and Alzheimer's disease (Testa and Bellacosa, 2001;Lu et al, 2003;Griffin et al, 2005;Robertson, 2005;Zdychova and Komers, 2005). In recent years, Akt has also been shown to impact microbial pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…T308 is phosphorylated by PI-dependent kinase (PDK) 1, and then at a second site, serine 473 (S473), located within the C-terminal regulatory domain of Akt by an as-yet unidentified kinase designated as PDK2 Stephens et al, 1998;Song et al, 2005). Phosphorylation of both T308 and S473 is required for full activation of Akt (Alessi et al, 1996).Due to its ability to affect cell fate and activities by influencing survival and other central regulatory pathways, Akt has become a prominent point of focus in various fields of research ranging from tumorigenesis to diabetes and Alzheimer's disease (Testa and Bellacosa, 2001;Lu et al, 2003;Griffin et al, 2005;Robertson, 2005;Zdychova and Komers, 2005). In recent years, Akt has also been shown to impact microbial pathogenesis.…”
mentioning
confidence: 99%